Identification and prevalence of swine pasivirus 1 in eastern Romanian pig farms. (May 2017) - Zaulet, Mihaela; Petrovan, Vlad; Birladeanu, Andrada M.; Stoian, Ana Maria M.; Kevorkian, Steliana E. M.; Nichita, Cornelia; Eloit, Marc; Buburuzan, Laura
Swine pasivirus 1 (SPaV-1) was first detected in the feces of healthy pigs in France as a new species in family Picornaviridae . We investigated the presence, distribution, and genetic variability of this virus in 7 geographic areas with intensive pig breeding farms in eastern Romania. A total of 564 porcine specimens, including 82 fecal specimens and 482 pools of organs, were collected from healthy pigs in different stages of production from pathogen-free swine farming units. The virus was found in 6 of 7 areas investigated. Of the 564 samples analyzed, 218 were positive for SPaV-1, with the highest prevalence of the virus in organ homogenates (39% positive) followed by feces (37% positive). The highest susceptibility to infection was found in nurseries (50% positive in both the first and second months of feeding). Sequencing analysis of VP0 revealed 3 different Romanian sequences. The phylogenetic investigations suggest that the Romanian sequences cluster with other Pasivirus strains selected from the GenBank database, forming a separate clade from other Picornaviridae genera and defining the described Pasivirus .